Better management practices in fish farming through Women Self Help Groups in Odisha, India - Eriksson, Hampus (WorldFish, 2022)
One visionary policy change & one innovative flagship program of the Government involving multiple Departments could socio- economically empower tens of thousands of women organized under self-help groups by engaging them in nutrition-sensitive fish farming activities in village public water tanks. In 2018, Government of Odisha in India brought a policy change for long-term leasing (3-5 years) of village public water tanks to women self-help groups (SHGs) for fish production. Three Departments (Fisheries & ARD; Mission Shakti and Panchayati Raj & Drinking Water) joined hands for this inter-departmental convergence program which is technically supported by WorldFish under its collaboration with Government of Odisha. As a result, nearly 10,000 women SHGs started farming fish in these village tanks in the nook and corner of the state over the last 4 years. The video captures the various BMPs practiced by WSHGs under the scheme.